Embryological studies of Magonia pubescens (Dodonaeaeae, Sapindaceae): development of male and female gametophytes in both floral morphs and its phylogenetic implications - González, Valeria Vanesa (2017)
Magonia pubescens A.St.-Hil. (Dodonaeaeae, Sapindaceae) is a monoecious species exhibiting two floral morphs, namely staminate flowers, with gynoecium reduced to a pistillode, and morphologically hermaphrodite but functionally pistillate flowers. It presents the basic type of antheral wall development. Microsporogenesis is normal, forming tetrahedral and decussate tetrads. Anatomical differences in anthers between floral morphs become visible at the stage of callose wall degradation and release of tetrads. In staminate flowers, the endothecium develops fibrous thickening, and the two middle layers, the tapetum and the parenchymal septum that separates both locule, are degraded. At dehiscence, permanent calymmate tetrads are released. Magonia is the only genus of the family with this type of pollen unit. In pistillate flowers, the endothecium exhibits fibrous thickening only in three to five cells on the dorsal loculus, and only the inner middle layer collapses. The septum that separates both locules remains unaltered, the stomium is non-functional, mature anthers are indehiscent and show collapsed tetrads. In staminate flowers, the gynoecium is reduced to a tricarpellar pistillode, trilocular, with ovules that degenerate after megasporogenesis. In pistillate flowers, the gynoecium has a tricarpellary ovary, with six to eight ovules per carpel; they are campylotropous, bitegmic, mixed crassinucellate, and exhibit a well-developed obturator. The phylogenetic implications of these embryological characters are discussed in the context of the family.